RESCUING POLITICS FROM LYING AND HYPOCRISY: UTILITY AND TRUTH IN JEREMY BENTHAM’S THOUGHT - Bourcier, Benjamin (Ethics, Politics & Society, 2023)
As a utilitarian philosopher, Jeremy Bentham (1748-1832) devoted most of his career to create a new institutional setting to promote the greatest happiness of the greatest number on the basis of the principle of utility. In doing so, Bentham committed himself not only to the value of utility but also to truth. Truth meant universal interest and denouncing all abuses of power and corruptions that sacrifice the interest of the greatest number. As two opponents of truth, lies and hypocrisy are the symptoms of the sacrifice of the universal interest and directly oppose the principle of utility. Yet, what is at stake in this opposition? How did Bentham value and analyze these two phenomenon? In this paper, I will explain how Bentham’s commitment against lying and hypocrisy in politics aims to support the truth of the utilitarian principle and demonstrates the wrongness of other moral principles.